The forging of moral leaders in social entrepreneurship: A comparative study from two public welfare organizations in China - Zhang, Shuo; Zhu, Huaixin; Lu, Jihai; Lu, Meili (Frontiers in Environmental Science, 2023)
Young people, including college students, are the main body for the main force of public welfare entrepreneurship and the effective force of future social entrepreneurs. How can college students, who are often self-made and lack entrepreneurial experience, social capital, and resources, grow up to be “moral leaders” of social entrepreneurship organizations? And what role does social entrepreneurship education play? Previous studies have not provided corresponding theoretical explanations to address these questions. This study uses as examples two public welfare organizations and their founders; namely, YinChao Pension Service Center in Yinzhou District, Ningbo City, and Ant Public Welfare Service Center in Yuyao City. The exploratory comparative research method of two cases is used, and the perspective is constructed based on personal significance. Through the open decoding analysis, this study refines the key elements of the individual growth of public entrepreneurs as “moral leaders,” including four stages: concept construction, moral conflict, relationship construction, and rule construction, as well as personal meaning construction strategy and public entrepreneurship education strategy. The research results not only explain how individuals grow up to be “moral leaders” in public welfare organizations through self-meaning construction in the context of public welfare entrepreneurship and the construction process from individual to organization morality systems but also provide a theoretical framework for cultivating successful public welfare entrepreneurs and a theoretical reference for the sustainable development of public welfare entrepreneurs and public welfare entrepreneurship education in colleges and universities.